2018
DOI: 10.1016/j.jcrs.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative complication rates in cataract surgery performed by ophthalmology resident trainees compared to staff surgeons in a Canadian academic center

Abstract: There were no differences in complication rates between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
26
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 21 publications
7
26
0
5
Order By: Relevance
“…Previous retrospective reviews comparing residents versus attending's cataract extractions have shown similar outcomes and complication rates overall. 18,25 Similar outcomes were also found when comparing attending and resident-performed tube shunt procedures. 19 Interestingly, Low et al 18 comment that residents who are in their initial 5-to 8-week training period in cataract surgery had higher rates of complications when compared with their supervising attending.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Previous retrospective reviews comparing residents versus attending's cataract extractions have shown similar outcomes and complication rates overall. 18,25 Similar outcomes were also found when comparing attending and resident-performed tube shunt procedures. 19 Interestingly, Low et al 18 comment that residents who are in their initial 5-to 8-week training period in cataract surgery had higher rates of complications when compared with their supervising attending.…”
Section: Discussionsupporting
confidence: 54%
“…As shown in previous studies, having experienced surgeons to train residents in a new surgical technique has been beneficial in reducing complications in the operative setting. 14,18 Additionally, residency wet-laboratory workshops, review of surgical videos prior to cases, and close supervision from attending surgeons may also lead to more efficient surgical time management while maintaining low complication rates. 19 Microhyphema, or suspended red blood cells in the anterior chamber, is an expected observation in the first 2 weeks following phaco-KDB due to blood reflux from Schlemm's canal, 10 and often does not affect the final IOP or best corrected vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CCC phase and nuclear extraction phase are both important surgical phases that cannot be regarded as identical to incision creation, cortical aspiration, or lens insertion. For example, from a surgical skills training perspective, the rate of surgical complications that developed in these two phases is clearly higher than in other phases 19 . The rate that the model confused the CCC phase with the nuclear extraction phase was almost zero, indicating a strong capability to distinguish phases.…”
Section: Discussionmentioning
confidence: 93%
“…8,10,21 This is consistent with several recent studies which have demonstrated similar complication rates and outcomes, when comparing trainees and attendings at academic centers. 24,25 However, the recovery period was prolonged, with the majority reaching significant VA improvement only after post-operative month three. While some did experience post-operative complications, most of these resolved within the first month after PPV, and the majority had no significant impact on final visual acuity.…”
Section: Discussionmentioning
confidence: 99%